The International Alcohol Control Study: Methodology and implementation. (2nd January 2018) - Huckle, Taisia; Casswell, Sally; Mackintosh, Anne‐Marie; Chaiyasong, Surasak; Viet Cuong, Pham; Morojele, Neo; Parry, Charles D. H.; Meier, Petra; Holmes, John; Callinan, Sarah; Piazza, Marina; Kazantseva, Elena; et al.
Abstract: Introduction and Aims: The International Alcohol Control (IAC) Study is a multi‐country collaborative project to assess patterns of alcohol consumption and the impact of alcohol control policy. The aim of this paper is to report the methods and implementation of the IAC. Design and Methods: The IAC has been implemented among drinkers 16–65 years in high‐ and middle‐income countries: Australia, England, Scotland, New Zealand, St Kitts and Nevis, Thailand, South Africa, Peru, Mongolia and Vietnam (the latter four samples were sub‐national). Two research instruments were used: the IAC survey of drinkers and the Alcohol Environmental Protocol (a protocol for policy analysis). The survey was administered via computer‐assisted interview and the Alcohol Environmental Protocol data were collected via document review, administrative or commercial data and key informant interviews. Results: The IAC instruments were readily adapted for cross‐country use. The IAC methodology has provided cross‐country survey data on key measures of alcohol consumption (quantity, frequency and volume), aspects of policy relevant behaviour and policy implementation: availability, price, purchasing, marketing and drink driving. The median response rate for all countries was 60% (range 16% to 99%). Where data on alcohol available for consumption were available the validity of survey consumption measures were assessed by calculating survey coverage found to be 86% or above. Differential response bias was handled, to the extent it could be, using post‐stratification weights. Discussion and Conclusions: The IAC study will allow for cross‐country analysis of drinking patterns, the relationship between alcohol use and policy relevant behaviour in different countries.